Loose parts learning based on local wisdom at Pertiwi Bina Siswa Kindergarten - Khusnul Laely; Wahyu Nofiyanti; Lusi Handayani; Siti Irchamiyah; Abdurahman Hadi Saleh; Fauzan Rukmana (Universitas Muhammadiyah Magelang, 2022)
The issues that occur in TK Pertiwi Bina Siswa are monotonous learning activities in their everyday activities and teachers use media that they must purchase and do not employ learning materials that are available in the surrounding environment. These issues motivate the authors to engage in community empowerment to educate teachers and parents about the use of loose parts, which are learning tools that can be found in the environment. FGD activities, socializing, training, and mentorship were the steps of this program. The program's finding suggests that partners (parents and teachers) can use loose parts from the environment to design learning activities that optimize children's potential and growth.